Business - Pride, William M.; Hughes, Robert J.; Kapoor, Jack R. (Boston : Houghton Mifflin, 1999)
This book is about: American business today; management and organization; The human resource; Marketing; Information for business strategy and decision making; Finance and investment; ...
Keywords: Business enterprises; Industrial management; Industrial management -- United States; Business enterprises -- United States; Business